Effect of flux addition on the microstructure and tensile strength of dissimilar weldments involving Inconel 718 and AISI 416. (15th December 2015) - Devendranath Ramkumar, K.; Dev, Sidharth; Saxena, Vimal; Choudhary, Ayush; Arivazhagan, N.; Narayanan, S.
Abstract: This research work articulates the microstructural features of the dissimilar weldments involving Ni based superalloy Inconel 718 and martensitic stainless steel, AISI 416 that is difficult to weld. Autogenous tungsten inert gas (TIG) welding was carried out with and without using flux to fabricate these bimetallic combinations. Microstructure at the fusion zones and the interfaces were characterized using optical and scanning electron microscopy. The results depicted the presence of fine martensite at the heat affected zone (HAZ) of AISI 416 and the formation of unmixed zone containing secondary phases at the HAZ of Inconel 718. Similarly, the formation of Nb rich eutectics along with sulfides was witnessed at the fusion zone of both the weldments. Owing to the low heat input witnessed during the flux assisted TIG welding, the Nb segregation was found to be minimal. Tensile studies reported that the fracture occurred at the fusion zone in both the cases. It was inferred from the tensile studies that the joint strength of the weldments with flux addition was greater than the ones without flux. This study demonstrated that dissimilar joints with complete penetration could be achieved in single pass using the TIG welding process with the aid of flux. Graphical abstract: Highlights: Welding of AISI 416 which is difficult to weld, with Inconel 718 for the first time Comparison of dissimilar joints obtained from autogenous TIG welding with and without flux Full penetration joints of Inconel 718 and AISI 416 in single pass using ATIG welding Formation of Nb rich phases at the fusion zone in both the weldments Greater tensile strength was reported for ATIG weldments.